2015
DOI: 10.1002/alr.21687
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of symptom profiles from a polyp vs an eosinophilic‐based classification of chronic rhinosinusitis

Abstract: Introduction Chronic rhinosinusitis (CRS) is likely a biologically heterogeneous disease process. Current guidelines propose subclassification using polyp status while others propose using mucosal eosinophilia. We hypothesized that appropriate CRS subclassification would increase homogeneity of baseline symptoms, and identify characteristic symptoms of each subtype. Methods 57 CRS patients undergoing surgery prospectively completed a preoperative battery of 73 questions relating to symptoms including the SNO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 47 publications
0
40
0
1
Order By: Relevance
“…9, 33 On electronic medical records review, clinical features including medication prescriptions were extracted. As shown in Table 1, patients in the high-IgD group more frequently had CRSsNP compared with the low-IgD cohort (75.0% versus 43.7%, respectively, P =.05).…”
Section: Resultsmentioning
confidence: 99%
“…9, 33 On electronic medical records review, clinical features including medication prescriptions were extracted. As shown in Table 1, patients in the high-IgD group more frequently had CRSsNP compared with the low-IgD cohort (75.0% versus 43.7%, respectively, P =.05).…”
Section: Resultsmentioning
confidence: 99%
“…In a cohort of 126 CRS patients, Banjeri and colleagues found that nasal obstruction and hyposmia/anosmia were more significantly associated with CRSwNP while facial pain/pressure was more prevalent in CRSsNP patients 8 . Additional studies of CRS patients at separate tertiary care centers found CRSwNP patients were more likely to report rhinorrhea, severe nasal congestion and loss of smell/taste than patients with CRSsNP 9, 10 . However, in both studies, there was still a considerable overlap in symptoms reported by both CRSsNP and CRSwNP patients, thus emphasizing the need for additional criteria to diagnose CRSwNP.…”
Section: Clinical Characteristicsmentioning
confidence: 98%
“…It remains difficult to distinguish eosinophilic and non-eosinophilic nasal polyps by clinical symptoms alone. A recent study examining 57 CRS patients who underwent surgery at a tertiary care facility found that ear pain, sneezing, severe difficulty breathing through the nose, severe nasal congestion, and bothersome loss of taste/smell were significantly more likely to be reported in patients with eosinophilic compared to non-eosinophilic nasal polyps 10 . The duration of sinus symptoms is also critical to ascertain, as symptoms lasting greater than 12 weeks are consistent with chronic rhinosinusitis while those lasting less than 4 weeks are more concerning for an acute infectious process.…”
Section: Recommendation For Information To Be Obtained To Determine Tmentioning
confidence: 99%
“…8 Using these thresholds, 23%, 36% and 15% of CRSsNP ET showed type 1, 2 and 3 inflammation, based on the expression of IFN-γ, CLC and IL-17A, respectively (Fig. 1C).…”
Section: To the Editormentioning
confidence: 98%